"The attendant sacrifices are more than I can make" ─ Anxiety of Influence and European Colonial Contact in the 19th Century (KULT_online, 2009)
Beginning with Europe’s confrontation with the wider world during voyages of discovery and expeditions between the 16th and 18th centuries, the literary and cultural studies scholar Michael C. Frank reconstructs a "History of the Anxiety of Cultural Influence", a phenomenon that reaches its apogee in the colonialism of the 19th century. On the basis of a heterogeneous corpus of texts that includes fictional adventure and travel novels by Herman Melville, H. Rider Haggard, and Joseph Conrad, as well as historical letters of correspondence, travel reports, philosophical essays, and legal documents, the author portrays the ambivalent and conflicting relationship between the desire to discover the new and unknown, on the one hand, and the fear of losing one’s own sense of identity and comprehension of one’s own culture, on the other. A sense of inner stability can be achieved, but only when one adopts strategies to disassociate oneself from the surrounding foreign environment.